Implementation of Training Strategies, Financial Management, Human Resource Management, Business Management, Layer Chicken - Wijayanti, Tri Cicik; Kurniaty, Kurniaty; Sawitri, Dyah; Anjeli, Maya Rupa; Rini, Yeni Tata; Bin Abdul Satar, Abdul Hadi (Institute of Education and Social Research, 2024)
This article explores the implementation of financial management, human resource management (HRM), and business management training strategies in the context of layer chicken farming in Indonesia. Using a case study method, this research investigates best practices and challenges faced in implementing these strategies. The findings indicate that training in financial management, HRM, and business management significantly enhances operational efficiency and profitability of layer chicken farming businesses. However, the implementation of these strategies also encounters several obstacles such as limited resources, resistance to change, and a lack of understanding of the importance of effective management. This article provides valuable insights for layer chicken farming business owners and other stakeholders to strengthen management practices in the poultry industry. Further steps are also suggested to address the challenges encountered in implementing these strategies.